EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA - Suhana, Suhana; Khosmas, Aminuyati; Khosmas, Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the effectiveness of the implementation of cooperative learning type teams games tournament (TGT) on the results of students' study VII class IPS Junior High School Islamic Bawari Pontianak. The research method used is experimental research method with the form of research used is Quasi Experimental Design. The data source of this research is the students of class VII A and B in Islamic Junior High School Pontianak and the data is Number of students of class VII Islamic Junior High School Bawari Pontianak Academic Year 2017/2018, The average value of student learning outcomes before and after follow cooperative learning type teams games tournament and conventional learning (assignment) class VII Islamic Junior High School Bawari Pontianak Year Teaching 2017/2018, planning, implementation and evaluating of learning models that teachers apply in social science learning. The result showed that the experimental class study result was 71,11 higher that the control class with has an average value of 60,60. Based on T-test, the value of sig (2-tailed) is 2,416 < 2,066, then according to the basic of making in the test independent sample T-test, then it can be concluded Ho rejected and Ha accepted, which means there is a difference between the learning averages of class A and B. The effectiveness of applying cooperative learning type teams games tournament with effect size of 0.81 and high categorization.Keywords : Cooperative Learning  Type Teams Games Tournament, Learning Results, and social science subjects.